Abusive head trauma among children in Alaska: a population-based assessment - Parrish, Jared; Baldwin-Johnson, Cathy; Volz, Margaret; Goldsmith, Yvonne (2013)
BackgroundSerious physical abuse resulting in a traumatic brain injury (TBI) has been implicated as an underreported cause of infant mortality. Nearly 80% of all abusive head trauma (AHT) occurs among children <2 years of age, with infants experiencing an incidence nearly 8 times that of 2-year olds.ObjectiveThis study describes the validation of the CDC Pediatric Abusive Head Trauma (PAHT) definitions when applied to a multi-source database at the state level and provides a robust annual incidence estimate of AHT among children <2 years of age in Alaska.DesignAHT cases among children residing in Alaska during 2005–2010 were identified by applying the PAHT coding schema to a multi-source database which included vital death records, the Violent Death Reporting System (AK-VDRS), the Maternal Infant Mortality Review – Child Death Review (MIMR-CDR), the Alaska Trauma Registry (ATR), the inpatient Hospital Discharge Database (HDD) and Medicaid claims. Using these data, we calculated statewide AHT annual incidence rates.ResultsThe databases with the highest case capture rates were the ATR and Medicaid systems, both at 51%, followed by HDD at 38%. Combined, the ATR, HDD and Medicaid systems captured 91% of all AHT cases. The linkage and use of the PAHT definitions yielded an estimated sensitivity of 91% and specificity of 98%. During the study period, we detected an annual average incidence of 34.4 cases per 100,000 children aged <2 years (95% CI 25.1, 46.1) and a case fatality proportion of 22% (10/45). Among the AHT cases, 82% were infants. Significant differences (p < 0.05) in AHT were noted by age and race, but not by sex.ConclusionsIn Alaska, applying the CDC PAHT definition to the multi-source database enabled us to capture 49% more AHT cases than any of the individual database used in this analysis alone.